Living with bipolar disorder: A study of the lived experience of Saudi employees diagnosed with bipolar disorder in the workplace - Hessah Alzahrani (Saudi Journal for Health Sciences)
Background: Bipolar disorder (BD) is a mental health condition characterized by significant mood swings. These mood fluctuations can profoundly impact various aspects of an individual’s life, including their work functions. Despite the critical nature of understanding how BD affects workplace dynamics, there is a notable lack of research focusing on this area, especially within the context of Saudi Arabia. This gap in literature underscores the need for a detailed exploration of the experiences of Saudi employees living with BD. Aims: The primary goal of this study is to delve into the lived experiences of Saudi employees diagnosed with BD, focusing on the challenges they face in the workplace. By doing so, the study aims to provide a deeper understanding of how BD symptoms affect work performance, workplace relationships, and overall job satisfaction. Settings and Design: This qualitative study is set in Saudi Arabia, targeting employees diagnosed with BD. The design focuses on capturing the unique experiences and perspectives of individuals through semi-structured interviews, aiming to uncover the nuanced ways in which BD influences their work life. Materials and Methods: Fifteen participants aged between 24 and 48 years, diagnosed with BD, were selected for semi-structured interviews. Thematic analysis was employed to analyze the interview data, following the phases defined by Braun and Clarke, which include transcription, familiarization, coding, generating themes, reviewing themes, defining and labeling themes, and concluding the analysis. Statistical Analysis Used: Not applicable, as this study employs a qualitative research methodology, focusing on thematic analysis rather than quantitative statistical analysis. Results: Four main themes emerged from the analysis: The impact of BD symptoms on work performance and workplace relationships, stigma associated with BD in the workplace, the nature of work and its influence on BD symptoms, and strategies employed by individuals to manage their BD symptoms at work. Participants highlighted the importance of flexibility in work hours and the physical work environment, as well as the challenges faced during depressive episodes, particularly in occupations demanding high cognitive skills. Conclusions: The study reveals a complex interplay between the symptoms of BD and the workplace environment. It underscores the critical need for workplace flexibility and understanding to accommodate individuals with BD, aiming to enhance their productivity and maintain positive workplace relationships. Furthermore, the findings highlight the significance of addressing stigma and developing effective strategies for managing BD symptoms at work, contributing to a more inclusive and supportive work environment for individuals with BD.